Antiinflammatory Activity of Bangle Rhizome (Zingiber purpureum Roxb) Ethanol Extract on Rat Carrageenan Induced and Erythema Method - Mia Ariasti; Muhammad Eka Putra Ramandha; Sri Winarni Sofya (JURNAL FARMASI DAN ILMU KEFARMASIAN INDONESIA, 2025)
Background: Inflammation is a physiological response triggered by cellular damage, typically characterized by symptoms such as edema. Objective: This study was conducted to evaluate the anti-inflammatory activity of the ethanol extract of Bangle rhizome (Zingiber purpureum Roxb.) using the carrageenan-induced paw edema method and the UVB-induced erythema method. The most effective dose demonstrating significant anti-inflammatory activity was also determined. Methods: The bangle rhizome (Zingiber purpureum Roxb) was subjected to maceration using 96% ethanol. A total of 25 rats were randomly divided into five groups: negative control (0.5% CMC-Na), positive control (diclofenac sodium at 0.9 mg/200 g body weight), and treatment groups receiving ethanol extract of bangle rhizome at doses of 5, 10, and 20 mg/200 g body weight. In the carrageenan-induced method, the edema volume in the rat paw was measured following the administration of 0.8% lambda-carrageenan. In the erythema method, the degree of inflammation was assessed using UVB-induced erythema scoring. Results and Conclusion: Anti-inflammatory activity was observed at doses of 5, 10, and 20 mg/200 g body weight in the carrageenan model and at doses of 10 and 20 mg/200 g in the erythema model. The most potent anti-inflammatory effect was recorded at the dose of 20 mg/200 g body weight, which was comparable to the positive control in both models. The presence of flavonoids and steroids in the extract may contribute to the observed anti-inflammatory activity.